An exploratory study of Israeli start-up extrepreneur usage of the Internet - Shoham, Snunith; Baruchson-Arbib, Shifra; Gouri-Oren, Osnat (2006)
Contiene bibliografía
Keywords: Empresario; Israel; Internet